## 28 May 2016

### SBI Clerk 2016- Practice Reasoning Questions (Inequality) Based on Exam Pattern

SBI Clerk 2016- Practice Reasoning Questions (Inequality) Set-47:
Dear Readers, Important Practice Reasoning Questions with explanation for Upcoming SBI Clerk Exams was given here with explanation, candidates those who are preparing for those exams can use this practice questions.

Directions (Q. 1-4) In each of these questions, relationship between different elements is shown in the statements. The statements are followed by two conclusions.
a)   If only Conclusion I is true
b)   If only Conclusion II is true
c)   If either Conclusion I or II is true
d)   If neither Conclusion I nor II is true
e)   If both the Conclusions I and II are true

1). Statements    P>R, R < S ≤ X, Y =X
Conclusions        I. P<S    II. Y>R

2). Statements    Z = C, B<A = N, C<B
Conclusions        I. Z<B          II. N>Z

3). Statements    T<V = W, X≥Y, W>X
Conclusions        I. V>Y                    II. V<X

4). Statements    J≥K>P=R < N = S
Conclusions        I. S≥ P       II. J<R

Directions (Q. 5 -11) In these questions, relationship between different elements is shown in the statements. The statements are followed by conclusions.
a)   If only Conclusion I is true
b)   If only Conclusion II is true
c)   If either Conclusion I or II is true
d)   If neither Conclusion I nor II is true
e)   If both the Conclusions I and II are true

5). Statements    P≥Q<T, R<Q≥S, V≥T
Conclusions        I. R≥P                 II. S>V

6). Statements    P≥Q<T; R<Q≥S; V≥T
Conclusions        I. S≤P                  II. V>R

7). Statements    H<I≤J; R≥I >A
Conclusions        I. H<R                   II. A>H

8). Statements    R≥I≤ J, A<I
Conclusions        I. J>R           II. J>A

9). Statements    J = K≥L≤M, K<S, J>T
Conclusions         I. L<S          II. M>T

10). Statements P<R≥I=C, L>E≥R
Conclusions       I. E>C                   II. C = E

11). Statements B≤C =D>E, F>C
Conclusions       I. F≥B                  II. C≥E

:
1). b) 2). e) 3). a) 4). b) 5). b) 6). e) 7). a) 8). b) 9). a) 10). c) 11). c)

Explanation:

1). According to the question,
P > R
R < S <= X
Y = X
On the combing statements (i), (ii) and (iii), we get
P > R<S <=X =Y
Conclusions           I. P<S           (false)
II. Y>R         (true)
So, it is clear that only Conclusion II is true

2). According to the question,
Z=C
B<A = N
C<B
On the combing the statements (i), (ii) and (iii), we get
Z = C<B<A = N
Conclusions           I. Z<B          (true)
II. N>Z         (true)
So, it is clear that both Conclusion I and II are true

3). According to the question,
T < V = W
X> =Y
W >X
On the combing statements (i), (ii) and (iii), we get
T < V = W > X >= Y
Conclusions           I. V>Y         (true)
II. V<X         (false)
So, it is clear that only Conclusion I is true

4). According to the question,
J > = K>P = R<N = S
Conclusions          I. S>= P       (true)
II. J>R         (false)
So, it is clear that only Conclusion I is true

5). I from given statement,
R > Q < = P à R < = P
So, Conclusion I is not true
II. from given statement
S<= Q<T<=V à S<V
So, Conclusion II is true

6). I. from given statement,
P> =Q>=S à S<=P
So, Conclusion I is true
II. from given statement
V>=T>Q>R à V>R
So, Conclusion II is true

7). The given statements are
H<I<=J, R>=I>A
I. from given statement,
H<I<=R à H<R
So, Conclusion I is true
II. from given statement
H<I>A
So, no relation can be found between H and A.

8). I. from given statement,
R>=I<=J
So, no relation can be established between J and R
II. from given statement
A<I<=J à J>A
So, Conclusion II is true

9). I. given statements are,
J=K>=L<=M ; K<S; J>T
From given statements,
L<=K<S à L<S                                   (true)
So, Conclusion I is true
II. from given statement
T<J=K>=L<=M
So, no relation can be established between M and T

10). given statements are,
P<R>=I=C; L>E>=R
From given statements,
E>=R>=I=C àE>=C
E>C or E=C
So, either Conclusion I or II is true.

11). given statements are,
B<=C=D>E; F>C
From given statements,
B<=C<F or B<=F                                (false)
And B<=C=D>E;
C>=E                                                 (false)
So, neither Conclusion I nor II is true.